KONFIGURASI HUBUNGAN ANTARA SISTEM PRODUKSI, STRATEGI BISNIS, LINGKUNGAN KOMPETITIF DAN BUDAYA ORGANISASI PADA PERUSAHAAN MANUFAKTUR - Parwadi Moengin (Media Riset Bisnis & Manajemen, 2009)
This research discusses about the relationship between production system, business strategy, competitive environment and organization culture at manufacturing industry. The relationship is developed by using a method standar of cluster analysis based on four types of production system, six types of business strategy, four types of competitive environment and four types of organization culture.To do this research, fifty companies were surveyed through face to face interviews to get data about production system type, business strategy type, competitive environment type and organization culture type. Four kinds of relationship between production system, business strategy, competitive environment and organization culture were observed.Keywords : Production system, Business strategy, Competitive environment, Organization culture